Spatial-serial dependency in multivariate GARCH models and dynamic copulas: a simulation study - Klein Ingo; Köck Christian; Tinkl Fabian (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2009)
The serial dependency of multivariate financial data will often be filtered by considering the residuals of univariate GARCH models adapted to every single series. This is the correct filtering strategy if the multivariate process follows a so-called copula based multivariate dynamic model (CMD). These multivariate dynamic models combine univariate GARCH in a linear or nonlinear way. In these models the parameters of the marginal distribution (=univariate GARCH models) and the dependence parameter are separable in the sense that they can be estimated in two or more steps. In the first step the parameters of the marginal distribution will be estimated and in the second step the parameter(s) of dependence.To the class of CMD models belong several multivariate GARCH models like the CCC and the DCC model. In contrast the BEKK model, f.e., does not belong to this class. If the BEKK model is correctly specified the above mentioned filtering strategy could fail from a theoretical point of view. Up to now, it is not known which dynamic copula is incorporated in a BEKK model. We will show that if the distribution of the innovations (i.e. the residuals) of MGARCH models is spherical the conditional distribution of the whole MGARCH process belongs to the elliptical distribution family. Therefore estimating the dependence of a BEKK model by copulas from the elliptical family should be an appropriate strategy to identify the dependence (i.e. correlation) between the univariate time series. Furthermore we will show, that a diagonal BEKK model can be separated in its margins and a copula, but that this strategy falls short of investigating full BEKK models.
Keywords: 330; ARCH-Modell; Zeitreihenanalyse; Kopula (Mathematik); Finanzmarkt; Simulation; Theorie